Safety Assessment of Ship Collision with Piers under the Protection of Anti-Collision Floating Box Based on BIM Technology - Ying-hao Chen; Cheng Liu; Xue-feng Zhao; Fa-xiong Li (Advances in Civil Engineering)
In order to research the force state of the piers subjected to a ship collision under the protection of floating anti-collision facilities, this study uses nonlinear spring connections to simulate the impact of ship damping and incidental water quality in the collision area. BIM technology is used to realize a safety evaluation method for the anti-collision floating box protection when the ship is colliding with piers. Established a BIM-based parametric preprocessing model for ships, piers, and anti-collision facilities, and opened the interface with ABAQUS longitudinally. After realizing the parameter adjustment of the BIM model, the visual parameter adjustment can be realized without destroying the boundary conditions, load conditions, and meshing. Taking a rigid frame bridge as an example, the most disadvantage position of the bridge pier under ship collision is determined by the parameterization method. At the same time, multi-condition analysis was carried out on the ship impacting the pier anti-collision floating box at different angles, different tonnages, and different speeds. Finally, the analysis results are traced back to the BIM model, achieving the unified integration of BIM model information and finite element analysis results and the purpose of visual analysis of any working conditions. The results show that the use of BIM parameterization technology to achieve linkage with the finite element preprocessing model can improve the efficiency of multi-condition sensitivity analysis and achieve the purpose of visual dynamic adjustment. The safety assessment analysis of the pier under the protection of the anti-collision pontoon on the pier under various working conditions shows that the anti-collision pontoon effectively reduces the hazard of the ship colliding with the pier, and the impact force gradually increases with the change from the oblique collision to the frontal collision. The peak impact force increases with the weight of the ship and shows a nonlinear relationship, such that the peak value of impact force increases with the speed increase, and the speed and the peak values of impact force show basically a linear relationship.